Pengaruh Perceived Usefulness dan Perceived Ease of Use Terhadap Actual System Use (Studi pada Pengguna Aplikasi BNI Mobile di Kota Salatiga) - Dimas Ramadhan; Agung Budiatmo; Apriatni Endang Prihatini (Universitas Diponegoro, 2024)
Digitalization has an impact on the economy where digitalization changes people's transaction patterns in the financial sector. Following existing technological developments, banks are also innovating to create digital services, namely mobile banking. One of the banks in Indonesia that provides mobile banking services is Bank BNI. It is known that BNI mobile application users rarely use the application. So it is likely caused by factors such as perceived usefulness and perceived ease of use. This research aims to determine the influence of perceived usefulness and perceived ease of use on actual system use. Sampling used a non-probability technique with a purposive sampling method. The population of this research is BNI mobile banking application users at Salatiga City. The data was processed using the SPSS application by carrying out validity tests, reliability tests, correlation coefficient tests, coefficient of determination tests, simple and multiple linear regression analysis, t tests, and F tests. The results of this research are that perceived usefulness influences actual system use with an influence of 32 %, perceived ease of use influences actual system use by 42.4%, and perceived usefulness and perceived ease of use influence actual system use by 46.3%. The suggestion in this research is to evaluate the usefulness and ease of use provided by the BNI mobile banking application so that the use of the BNI mobile banking application can be increased.Keywords: Perceived Ease of Use, Perceived Usefulness, Actual System UseDigitalisasi memberi pengaruh pada perekonomian dimana digitalisasi mengubah pola transaksi masyarakat di sektor keuangan. Mengikuti perkembangan teknologi yang ada, bank juga turut berinovasi untuk menciptakan layanan digital yaitu mobile banking. Salah satu bank di Indonesia yang menyediakan layanan mobile banking adalah Bank BNI. Diketahui bahwa pengguna aplikasi BNI mobile jarang menggunakan aplikasinya. Sehingga kemungkinan disebabkan oleh faktor seperti perceived usefulness dan perceived ease of use. Penelitian ini bertujuan untuk mengetahui pengaruh perceived usefulness dan perceived ease of use terhadap actual system use. Pengambilan sampel menggunakan teknik non-probability dengan metode purposive sampling. Populasi penelitian ini adalah pengguna aplikasi mobile banking BNI di Kota Salatiga. Data diolah menggunakan aplikasi SPSS dengan melakukan uji validitas, uji reliabilitas, uji koefisien korelasi, uji koefisien determinasi, analisis regresi linear sederhana dan berganda, uji t, dan uji F. Hasil penelitian ini adalah perceived usefulness berpengaruh terhadap actual system use dengan pengaruh sebesar 32%, perceived ease of use berpengaruh terhadap actual system use sebesar 42,4%, dan perceived usefulness dan perceived ease of use berpengaruh terhadap actual system use sebesar 46,3%. Saran pada penelitian ini adalah untuk melakukan evaluasi mengenai usefulness dan ease of use yang diberikan melalui aplikasi mobile banking BNI sehingga penggunaan aplikasi mobile banking BNI dapat ditingkatkan.Kata Kunci: Perceived Ease of Use, Perceived Usefulness, Actual System Use